KOMUNIKASI INTERPERSONAL JRO KUBAYAN DENGAN JRO BENDESA DALAM MELAKSANAKAN TUGAS ADAT DI DESA ADAT TALEPUD-SEBATU, KECAMATAN TEGALLALANG, KABUPATEN GIANYAR - I Gede Bawa Sujana; Dewa Ketut Wisnawa; I Nyoman Alit Putrawan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Talepud Gianyar Traditional Village has a unique reality, namely adhering to two customary village government systems consisting of government with the spirit of Ancient Bali and Bali Dataran. Evidently, the Talepud Traditional Village was led by Jro Kubayan and Jro Bandesa. Even though the history of governance is different, the two of them still manage the traditional village according to their respective policies, so that there is quite a striking dualism of government in the Talepud Traditional Village. This study analyzes interpersonal communication as a space for peace that brings together the Jro Kubayan administration and Jero Bendesa Adat in carrying out customary government duties in Talebud Adat Village, Sebatu, Gianyar. The analysis is based on three problem formulations, namely why are there two government systems in the Talepud Traditional Village? how is the implementation of interpersonal communication between Jro Kubayan and Jro Bendesa in carrying out traditional tasks in the Talepud Traditional Village? and what is the impact of interpersonal communication between Jro Kubayan and Jro Bendesa on the implementation of traditional activities in the Talepud Traditional Village. The formulation of the problem is analyzed by functional and structural theory, interpersonal communication theory and S.O.R. communication theory. The results of this study indicate that the background of the dualism of traditional leadership in Talebut Traditional Village is based on the historical aspect, namely the acculturation of the hulu apad system (ancient Bali) and apanaga (Balinese Plains). Jro Kubayan and Jero Bandesa Adat are also seen as having a differentiation of duties and functions which together are very important to the community, namely, Jro Kubayan specifically becomes the leader for aspects of Hindu religious rituals, while Jro Bandesa focuses on the realization of executive duties in accordance with the applicable customary village regulations. The implementation of interpersonal communication between Jro Kubayan and Jro Bendesa fulfills the basic requirements of interpersonal communication consisting of communicators and communicants that involve both, messages are mostly non-verbal, feedback is seen unilaterally, namely only happening to Jro Kubayan through the act of refusing the treatment of traditional village officials , the media that is applied consists of formal media such as Pasangkepan and informal media such as small talk although it is not optimal, there are even obstacles such as physical, semantic, psychological, physical and human barriers. The impact of interpersonal communication consists of internal impacts as indicated by changes in people's attitudes and the quality of customary activities in the Talepud Traditional Village, as well as external impacts in the form of changes in communication with wawidayangan or pasemetonan traditional villages and changes in the image of Talepud Traditional Village in the eyes of other traditional villages. Keywords: Interpersonal Communication, Jro Kubayan, Jro Bendesa, Customary Tasks